2020
DOI: 10.1101/2020.06.07.20121939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mortality Analysis of COVID-19 Confirmed Cases in Pakistan

Abstract: Introduction: COVID-19, a novel disease, appeared in December 2019 in China and rapidly spread across the world. Till the second week of April 2020, high incidence (2.9/100,000) and cases fatality rates (1.7%) were observed in Pakistan. This study was conducted to determine the temporal and spatial distribution of the first 100 deaths attributed to COVID-19 in Pakistan and their associated demographic factors. Method: We conducted a descriptive epidemiological analysis of the first 100 deaths reported among R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The stimulation of adaptive immunity is dependent not only on the identification of a specific antigen receptor but also on key signals provided by the innate immune system. The decrease of de-novo production of T and B cells is a well-known age-associated immune system modification ( 13 ).…”
Section: Aging and Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulation of adaptive immunity is dependent not only on the identification of a specific antigen receptor but also on key signals provided by the innate immune system. The decrease of de-novo production of T and B cells is a well-known age-associated immune system modification ( 13 ).…”
Section: Aging and Adaptive Immunitymentioning
confidence: 99%
“…However, no evidence of a greater risk among pregnant women has been found ( 12 ). According to the literature, the death rate among hospitalized patients was 15%, with an average time from onset of symptoms to death of 14 days ( 13 ). Based on the data collected from Italy and China, Corona patients have a mortality rate of 2.3%, with more than half of the mortality reported in patients with age 50 years or older ( 14 ).…”
Section: Lung Complications and Their Mortality Rates With Respect To Agementioning
confidence: 99%
“…Focuses on asymptomatic individuals and high incidence sub-wards Monteiro, [124] India-Pune, Maharashtra Provides no relevant seroprevalence or IFR Sharma, [125] India-Punjab Provides no relevant seroprevalence or IFR Vignesh, [126] India-Tamil Nadu Provides no relevant seroprevalence or IFR Laxminarayan, [127] India-Tamil Nadu and Andhra Pradesh Provides no relevant seroprevalence or IFR Panchamia, [128] India-three states in Western India Focuses on elderly homes Conducted at a hospital/healthcare clinic/ICU Abbas, [135] Pakistan Focuses on healthcare workers Chaudhry, [136] Pakistan Provides no relevant seroprevalence or IFR Din, [137, p. 19] Pakistan Provides no relevant seroprevalence or IFR Peter, [138] Pakistan Provides forecasted estimates Waqar, [139] Pakistan Focuses on symptomatic individuals Zaidi, [140] Pakistan Focuses on working individuals Naiyar, [141] Pakistan-Gujrat, Punjab…”
Section: -36mentioning
confidence: 99%
“…In a study by Elizabeth [12] et al, older age was the most significant risk factor for death, followed by hematologic malignancies, immunosuppressive drugs, organ transplantation, uncontrolled diabetes mellitus, black race, and obesity. A study from Pakistan by Ambreen Chaudhry [13] et al found that the risk factors responsible for worse outcomes, defined as ICU admission, invasive mechanical ventilation (IMV), and death, were older age and the presence of comorbidities.…”
Section: Introductionmentioning
confidence: 99%